(untitled) (Al-Aasar, 2025)
In literature, existential themes reflect the difficulty of claiming one’s identity in a shattered modern world. In the face of existential uncertainty, existentialism emphasizes the value of emotional honesty, self-awareness, and sincerity while exposing the vulnerability of the human situation. Abjection is a physical and psychological reaction to that which threatens the sense of identity and rules and limitations we apprehend as the norm. This study aims to explore abjection in Louise Glück’s poetry from the theoretical lens of Kristeva’s theory of abjection. The three poems “The Empty Glass”, “Lamium”, “Mother and Child” from various collection of poem The Seven Ages (2001), The Wild Iris (1992) exemplify the engagement of loss, alienation, suffering, emptiness, and breakdown of identity. The study is qualitative in nature, paying attention primarily on the themes as well as the presence of abjection in the poems due to the challenge of boundaries between self and other.Through an examination of the sharp differences between expectations and reality, the disruption of societal rules, and the deep sensation of absence and loss, this research shows how Glück poetry expresses the existential struggle with emptiness. This study integrates to add deeper insight into works of Glück on how the battle for identity, fulfillment, and meaning in an indifferent and bizarre environment sheds light on the potent interplay between abjection and existentialism.